2014
DOI: 10.4049/jimmunol.1400968
|View full text |Cite
|
Sign up to set email alerts
|

IL-2–Inducible T Cell Kinase Tunes T Regulatory Cell Development and Is Required for Suppressive Function

Abstract: ITK is a key signaling mediator downstream of TcR, mediating T cell positive selection, innate T cell and CD4+ Th2/Th17 differentiation. Here we show that ITK also negatively tunes IL-2-induced expansion of Foxp3+ regulatory T cells (Treg). In vivo, Treg abundance is inversely correlated with ITK expression, and iTreg development is inversely dependent on ITK kinase activity. While Treg development normally requires both hematopoietic and thymic MHC class 2 (MHC2) expression, the absence of ITK allows Treg dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
3
36
2
Order By: Relevance
“…We therefore considered whether the inhibitory effect of PRN694 on colitis might be due to enhanced differentiation of Foxp3 + iTreg cells in the inhibitor-treated mice. Instead, analysis of T cells at 7-weeks post-transfer indicated that PRN694 significantly reduced the proportions of CD4 + T cells expressing Foxp3 compared to controls, a result consistent with the findings of Huang et al (14). This was evident in all organs examined (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We therefore considered whether the inhibitory effect of PRN694 on colitis might be due to enhanced differentiation of Foxp3 + iTreg cells in the inhibitor-treated mice. Instead, analysis of T cells at 7-weeks post-transfer indicated that PRN694 significantly reduced the proportions of CD4 + T cells expressing Foxp3 compared to controls, a result consistent with the findings of Huang et al (14). This was evident in all organs examined (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Specifically, Itk −/− T cells showed reduced IL-17A production and increased forkhead box P3 (Foxp3) expression following in vitro polarization (12, 13). In addition, Itk −/− T cells provided enhanced regulatory T cell (Treg)-mediated protection in an adoptive transfer model of colitis, due to their increased potential to upregulate Foxp3 (13), although another study found that Itk −/− Tregs were unable to protect against T cell mediated colitis (14). In spite of some of disparities between studies, in general, these findings have provided impetus for the development of small molecule ITK kinase inhibitors, with the intent of using them as treatments for atopic diseases, as well as for their potential as an immunosuppressant to block graft rejection or autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown ITK as a negative regulator of Foxp3 + Treg cell development1617, but its role in CD4 + Foxp3 − IL-10 + Tr1 cell development is unclear. To determine the role of ITK in Tr1 cell differentiation in vivo , we injected WT and Itk −/− IL-10 GFP /Foxp3 RFP dual reporter mice with an anti-CD3ε antibody that has been shown to stimulate pronounced Tr1 cell development through TCR activation in vivo 3.…”
Section: Resultsmentioning
confidence: 96%
“…Accordingly, Itk deficiency results in enhanced iTreg cell differentiation 67 . The absence of Itk also results in an increased tTreg cell frequency in vivo 68 , but it remains to be determined whether Pten-mediated repression of Akt is affected. An important downstream target of Akt is the tuberous sclerosis (TSC) complex that suppresses mTOR complex 1 (mTORC1) activation by functioning as a GTPase-activating protein for the small GTPase Rheb 69 .…”
Section: Tcr Signaling and Treg Cell Differentiationmentioning
confidence: 99%